Fire Your Stock Analyst! : Analyzing Stocks on Your Own. - Domash, Harry (FT Press Pearson Education [distributor], 2006)
This is simply the world's most useful book for personal investors who want to rely less on the so-called "experts" and more on their own€ intelligence and knowledge. The author presents systematic value and growth strategies that draw on the best ideas from more than 20 of the world's leading money managers -- and shows you how to implement each strategy step-by-step, using free or low-cost information available on€ the Internet.€ Domash introduces never-before-published advanced analysis strategies, shows how value investors really pick stocks, and presents new ways of quantifying a stock's risk. This book covers issues most books simply ignore, including how to evaluate a company's business plan and true financial strength, how to set your own target prices, and most important, when to sell.